A new cyclotriphosphazene appended phenanthroline derivative as a highly selective and sensitive OFF–ON fluorescent chemosensor for Al3+ ions. (September 2016) - Özcan, Emrah; Tümay, Süreyya O.; Alidağı, Hüsnüye Ardıç; Çoşut, Bünyemin; Yeşilot, Serkan
Abstract: A new type of fluorescent chemosensor based on a novel cyclotriphosphazene appended phenanthroline derivative was synthesized and its sensing behavior toward metal ions was investigated by UV/vis and fluorescence spectroscopies. Addition of an Al 3+ ion to an acetonitrile solution of the phenanthroline derivative exhibited a significant increase of fluorescence emission intensities, while 18 other metal ions induced no spectral changes. This phenanthroline derivative, as a candidate for an OFF-ON fluorescent chemosensor for Al 3+, was found to be highly selective and sensitive with a low limit of detection (1.825 μg L −1 ). Graphical abstract: Highlights: A new type of fluorescent chemosensor based on cyclotriphosphazene appended phenanthroline has been synthesized. The photophysical properties of the compounds have been studied in acetonitrile. The Fluorescence Sensing properties of the compounds have been studied in acetonitrile. Very selective and sensitive fluorescence sensor for detection of Al (III) has been obtained.